Nanopartikel TIO2 Dari Ekstrak Daun Kemangi (Ocimum Sanctum) Untuk Degradasi Metilen Biru - Dina Kartika Maharani; Rahma Nurisnaini (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
The part of the basil plant is the leaves which have various types of benefits if studied further. With the introduction of secondary metabolites, it can be said that basil leaves contain eugenol compounds. The eugenol compound can be used as a reducing agent in the synthesis of TiO2 nanoparticles. The precursor used in the synthesis of TiO2 is titanium isopropoxide which has an oxidation state of +4. By utilizing the green synthesis method, TiO2 was reacted with basil leaf extract and then characterized using XRD and FTIR. The resulting particle size is 10.86 nm. And FTIR shows a wave number of 874.59 which represents the Ti-O functional group. Photocatalytic activity can take advantage of the synthesis of TiO2 nanoparticles by placing the nanoparticles in a methylene blue solution which has a concentration of 20 ppm and varies based on contact time and adsorbent mass. Photocatalytic activity testing obtained a degradation percentage of 79%-84% which varied based on adsorbant mass and contact time. Varying the adsorbant mass and time results in a degradation percentage that increases with each additional mass but will not increase again if it has reached the optimum phase and can reduce the degradation percentage.